The Influence of Artificial Intelligence on Customer Retention in the Asian E-Commerce Market - Zi Jian Oh; Abayomi Tunde Odebunmi; Yun Ern Teoh; Wei Min Thoe; Yu Jing Toh; Yu Xuan Toh; Anees Janee Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Artificial intelligence (AI) has become a key driver in enhancing customer retention in e-commerce. This study examines the influence of AI-driven personalization, efficiency and convenience, and customer trust and loyalty on customer retention in Lazada’s Asian market. A quantitative research approach was employed, with data collected through an online survey of 150 Lazada users using convenience sampling. The survey measured key constructs using a five-point Likert scale, and IBM SPSS Statistics 27 was used for analysis. The regression results indicate that customer trust and loyalty (? = 0.694, p 0.001) have the strongest impact on customer retention, followed by personalization (? = 0.166), while efficiency and convenience (? = 0.062) have a minimal effect. The model explains 82.5% of the variance in customer retention (R² = 0.825), demonstrating strong predictive power. These findings highlight the importance of fostering trust and personalized experiences in AI-driven e-commerce strategies. While efficiency and convenience enhance the shopping experience, they play a lesser role in long-term retention. The study suggests that businesses should prioritize AI-driven trust-building strategies and culturally adapted personalization techniques to strengthen customer loyalty and sustain retention in competitive e-commerce environments.